2005
DOI: 10.1073/pnas.0407498102
|View full text |Cite
|
Sign up to set email alerts
|

HIV dynamics with multiple infections of target cells

Abstract: The high incidence of multiple infections of cells by HIV sets the stage for rapid HIV evolution by means of recombination. Yet how HIV dynamics proceeds with multiple infections remains poorly understood. Here, we present a mathematical model that describes the dynamics of viral, target cell, and multiply infected cell subpopulations during HIV infection. Model calculations reproduce several experimental observations and provide key insights into the influence of multiple infections on HIV dynamics. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
123
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 32 publications
10
123
0
Order By: Relevance
“…To characterize the genome of clonal viruses, DNA was extracted from infected cell pellets, and genomic regions of Х1,300 bp in gag-pol and env were amplified from proviral DNA and sequenced. For the 127 clonal viruses evaluated (25,19,12,19,34, and 18 clones, respectively, for patients 1 to 6), base calls were unambiguous at all positions sequenced. In the course of the studies, proviral DNA from only two infected wells produced sequences in which ambiguous bases were identified, and these samples were excluded from analysis.…”
Section: Isolation Of Clonal Viruses From Plasma Of Patients Infectedmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the genome of clonal viruses, DNA was extracted from infected cell pellets, and genomic regions of Х1,300 bp in gag-pol and env were amplified from proviral DNA and sequenced. For the 127 clonal viruses evaluated (25,19,12,19,34, and 18 clones, respectively, for patients 1 to 6), base calls were unambiguous at all positions sequenced. In the course of the studies, proviral DNA from only two infected wells produced sequences in which ambiguous bases were identified, and these samples were excluded from analysis.…”
Section: Isolation Of Clonal Viruses From Plasma Of Patients Infectedmentioning
confidence: 99%
“…To the extent that the two RNA genomes are distinct, recombination generates viral DNA coding for genetic information different from that of the two parental strains (9,12,16,17). Numerous studies performed in vitro have documented the occurrence of recombination during HIV-1 replication (6,27,38,39,46,47,54).…”
mentioning
confidence: 99%
“…Much work has been done using ordinary differential equation (ODE) and partial differential equation (PDE) models (Arnaout et al, 2000;De Boer and Perelson, 1989;Dixit and Perelson, 2005;Kirschner, 1996;Wodarz and Nowak, 1998). These models have explained different aspects of the dynamics of the virus-immune system interaction.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of HIV dynamics models assume that each CD4+ T cell is infected by a single HIV strain, Dixit and Perelson [30] have shown that with the progression of HIV infection multiple infections become very likely.…”
Section: Modelsmentioning
confidence: 99%